(untitled) (Physical Education, Health and Social Sciences, 2025)
Metal-based nanoparticles (M-NPs) have emerged as promising nanomaterials with exceptional potential in diverse biomedical applications due to their unique physicochemical, biological, and functional properties. This mini-review provides a comprehensive overview of recent advancements in the synthesis, functionalization, and biomedical utilization of M-NPs. The review highlights key applications of M-NPs in antimicrobial therapy, drug delivery, cancer treatment, biosensing, and diagnostic imaging. Special emphasis has been placed on recent innovations, including smart/functionalized nanoparticles, surface modification strategies for targeted delivery, nano-hybrids, multi-metallic systems, and metal-organic frameworks (MOFs), which have significantly enhanced the therapeutic performance of M-NPs. The review also discusses how these nanoparticles work, including creating ROS, breaking down membranes, binding to DNA/RNA, changing proteins, and causing cell death, which all contribute to their effectiveness in medicine. However, significant clinical barriers such as toxicity, biosafety issues, and regulatory limitations have so far hampered their progress. Thereafter, the future vantage point for the advancement remains on the introduction of safer methods, personalized nanomedicine, nanoenabled regenerative medicine, and multifunctional intelligent NPs and the interviewing way from the laboratory research to the clinic. In general, metal-based nanoparticles are a powerful and promising platform in nanomedicine that will be part of future healthcare strategies.